Melatonin Alleviates Low-Temperature Stress via ABI5-Mediated Signals During Seed Germination in Rice (Oryza sativa L.) - Li, Ruiqing; Jiang, Meng; Song, Yue; Zhang, Huali (Frontiers in Plant Science, 2021)
With increasing areas of direct sowing, low-temperature (LT) stress drastically affects global rice production. Exogenous applications of melatonin (MT) serve as one of the effective ways to improve seed germination under various stress conditions. In this study, we found that MT treatment greatly improved the LT stress-induced loss of germination percentage and the weak performance of seedlings under LT of constant 20°C (LT20). This was largely dependent on the activated antioxidant system and enhanced activities of storage substance utilization-associated enzymes. Moreover, we also detected that exogenous feeding of MT significantly increased the biosynthesis of gibberellin (GA) and endogenous MT but simultaneously inhibited the accumulation of abscisic acid (ABA) and hydrogen peroxide (H2O2) under LT20 stress. These results suggested that MT had antagonistic effects on ABA and H2O2. In addition, MT treatment also significantly enhanced the expression of CATALYSE 2 (OsCAT2), which was directly regulated by ABA-INSENSITIVE 5 (OsABI5), a core module of ABA-stressed signals, and thus promoting the H2O2 scavenging to reach reactive oxygen species (ROS) homeostasis, which consequently increased GA biosynthesis. However, in abi5 mutants, OsCAT2 failed in response to LT20 stress irrespective of MT treatment, indicating that OsABI5 is essential for MT-mediated seed germination under LT20 stress. Collectively, we now demonstrated that MT showed a synergistic interaction with an ABI5-mediated signal to mediate seed germination, partially through the direct regulation of OsCAT2.